2006
DOI: 10.1111/j.1460-9568.2005.04555.x
|View full text |Cite
|
Sign up to set email alerts
|

Anp32e/Cpd1 regulates protein phosphatase 2A activity at synapses during synaptogenesis

Abstract: Anp32e/Cpd1, a member of the acidic nuclear phosphoprotein (Anp)32 family, is characterized by the presence of an amino terminal domain containing four leucine-rich repeats and a carboxyl-terminal low-compositional complexity acidic region. In previous studies performed to understand the biological role of Anp32e/Cpd1, we showed a predominant presence of Anp32e/Cpd1 in the nucleus. However, when Anp32e/Cpd1 is in the cytoplasm, it co-localizes spatially with protein phosphatase 2A (PP2A) near cell membranes, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 44 publications
0
25
1
Order By: Relevance
“…ANP32E was found to be differentially expressed in triple-negative medullary basal-like breast cancer (16) and is a member of the wound response signature (17), which has been found to be predictive of poor prognosis. Whereas it has been reported to regulate the activity of the tumor suppressor protein phosphatase PP2A in cerebellar synatogenesis (18), we know of no study that has reported such a role for it in breast cancer. Expression of both DSC2 and ANP32E is also associated with p53 mutation (19), which is predictive of poor patient outcome and is most frequently observed in patients with basal-like or ERBB2 + breast cancer.…”
Section: Resultsmentioning
confidence: 84%
“…ANP32E was found to be differentially expressed in triple-negative medullary basal-like breast cancer (16) and is a member of the wound response signature (17), which has been found to be predictive of poor prognosis. Whereas it has been reported to regulate the activity of the tumor suppressor protein phosphatase PP2A in cerebellar synatogenesis (18), we know of no study that has reported such a role for it in breast cancer. Expression of both DSC2 and ANP32E is also associated with p53 mutation (19), which is predictive of poor patient outcome and is most frequently observed in patients with basal-like or ERBB2 + breast cancer.…”
Section: Resultsmentioning
confidence: 84%
“…Our investigation showed that tissues from a mutant mouse whose Anp32e deficiency was validated by quantitative RT-PCR produced an identical band pattern to that of wild-type tissues upon western blotting. Such a result suggests that the antibody and oligobody used in previous publications [16], [19] may not recognize Anp32e at all but rather an unknown factor(s).…”
Section: Discussionmentioning
confidence: 89%
“…Diverse Anp32 family members exert their functions by modulating phosphatase activity [19], [20], [21], mRNA stability [22], [23], [24], intracellular transport [22], [25], [26], caspase activation [8], [9], [10], [11], and/or chromatin modification [27], [28], [29]. Based on this accumulated literature, it is probable that the Anp32 factors control multiple cellular activities in a broad range of physiological contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Both proteins have been described as inhibitors of protein phosphatase 2A activity [10], [11], with CPD1 thought to modulate phosphatase activity at synapses during synaptogenesis [11]. Besides these properties, LANP and other ANPs have also been proposed to play a role in the regulation of pathways involved in signaling [12], apoptosis [13], [14] and RNA transport and stability [15].…”
Section: Introductionmentioning
confidence: 99%